2015
DOI: 10.1007/s11657-015-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

Swedish osteoporosis care

Abstract: The objective of this study was to review and describe the current state of Swedish osteoporosis care and to highlight ongoing challenges. This report encompasses quantitative health outcomes based on Swedish registry data as well as organizational and management aspects. Swedish osteoporosis care is characterized by a significant burden of disease, difficulties in identifying high-risk patients, and fragmented pathways for patients in need of secondary fracture prevention. This report aimed to describe the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…This "treatment gap" has been estimated at 23-80% depending on sex and age group in Sweden [6]. Similar estimates have been found in the UK, Germany, US and Spain [3,7].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…This "treatment gap" has been estimated at 23-80% depending on sex and age group in Sweden [6]. Similar estimates have been found in the UK, Germany, US and Spain [3,7].…”
Section: Introductionsupporting
confidence: 71%
“…A 10-year maximum treatment length was assumed as this would reflect that a proportion of patients remain on treatment for longer periods in clinical practice. For example, a Swedish register study showed that, using a 1-year permissible gap between prescriptions, the proportion of patients still persistent to treatment at 5 years after treatment start is about 20% and it is not unreasonable that a proportion of patients are treated beyond 5 years [6]. Also, safety and effect are documented in 7-10 years in clinical studies [29].…”
Section: Treatment Efficacy and Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…This arises because of lower fracture risks in the younger populations, despite having a recent fracture and low BMD T-score. In clinical practice, it is expected that the proportion of the target patient population within the young groups is small since fracture risks increase exponentially with age, and the mean age in patient initiating osteoporosis treatment is around 72 years [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion persistent to teriparatide, an injectable bone-forming agent administered daily, has been estimated to 70% after 1 year [ 22 ]. Persistence with romosozumab was assumed to be higher than teriparatide since less frequently administered drugs have been shown to be associated with greater persistence [ 23 ]. Persistence for each time point and treatment is shown in Supplementary Table 5 .…”
Section: Methodsmentioning
confidence: 99%